Neon prey [compact disc, unabridged] - Sandford, John, 1944 February 23- (Penguin Audio, 2019)
When a seemingly minor investigation leads to the discovery of trophies from a score of murders, Lucas Davenport lands on the trail of an enigmatic killer who has been able to operate below the radar for years.